Economic growth and poverty reduction in Indochina: lessons from East Asia - Bautista, Romeo M. (International Food Policy Research Institute, 1999)
Differences and similarities in the development paths taken by six East Asian economies (Indonesia, Malaysia, Philippines, Thailand, South Korea, and Taiwan) provide a fertile ground for policy analysis from which important lessons are drawn and major challenges identified for the Indochinese transitional economies (ITEs for short, including Cambodia, Laos, Myanmar, Viet Nam, and China) in advancing the twin objectives of economic growth and poverty reduction. The paper first examines the comparative growth performance of these two groups of Asian economies over the period 1970-1997, describes the significant features of transition and development in the ITEs, and analyzes the relationship between development performance and policies among the East Asian countries. The following major policy challenges for ITEs are discussed towards the end of the paper: (1) sustaining reform efforts toward market orientation; (2) promoting broad-based agricultural growth; (3) supporting labor-intensive, export-oriented industries; (4) dealing with macroeconomic imbalances; and (5) building a strong financial system.